Early Marriage : Ethnographic Study in North Securai Village Babalan District Langkat Regency - Tusiana, Yona; Zuska, Fikarwin (Indonesian Journal of Medical Anthropology, 2020)
This study discusses the lives of married couples, from before marriage until after marriage. The purpose of this study is to describe why early marriage occurs in North Securai Village, Babalan Sub-District, Langkat Regency, and also the implications of early marriage on her home life. This research uses ethnographic methods. Methods used in digunakan data collection are observation of participation and in-depth interviews. The results of the study are many things that are the cause of early marriage, such as from their own desires until the marriage is forced to be done, as well as because of MBA (Married By Accident).